PENGARUH KENYAMANAN TRANSAKSI DAN SALES PROMOTION TERHADAP KEPUTUSAN PEMBELIAN ULANG PRODUK FASHION SHOPEE DI KEBUMEN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING - Mustofa, Ridho; Muhammad, Baehaqi (Politeknik Sawunggalih Aji, 2024)
This research aims to test and analyze the influence of Transaction Convenience, Sales Promotion on Repurchase Decisions for Shopee Fashion Products in Kebumen with Customer Satisfaction as an Intervening Variable. Data was collected by filling out a questionnaire on a Likert scale by 180 respondents, who were selected using the purpcosive sampling method. Data analysis was carried out using descriptive and statistical analysis techniques. To test the structural model, a Structural Equation Model (SEM) with the Partial Least Square (PLS) method is used, which includes outer model testing, inner model testing, hypothesis testing, as well as evaluating the goodness and suitability of the model using the SmartPLS3 program. The findings show that Transaction Convenience and Sales Promotion have a significant influence on Customer Satisfaction. Then transaction convenience and sales promotions also have a significant impact on repeat purchase decisions. Apart from that, Customer Satisfaction also has a significant influence on Repeat Purchase Decisions. Transaction convenience also has a significant effect on repurchase decisions through customer satisfaction as a mediator variable, as well as sales promotion